A Comparative Study of the Algorithms used to Plagiarism Detection (Journal of Hama University, 2019)
Science is one of the pillars of nation building and progress. No one can deny that the social and economic growth of any nation linked to science and scientific research, which is the main pillar in the development of any society. Unfortunately, the phenomenon of plagiarism spread in the field of scientific research, some researchers adopted the ideas and writings of another person as their own, taking advantage of technical and technological advances that made access to vast information possible through the Internet.Plagiarism was not confined to scientific research, but extended to all aspects of life. Plagiarism became in doctoral and master's dissertations, books, music, pictures, art articles and drawings. Due to the negative effects of this phenomenon on universities and scientific research centers and the adoption of large numbers of students on the Internet in there, university project has emerged the need to secure systems capable of detecting plagiarism. The previous studies classify the types of algorithms used in these systems into two basic types, external, where the suspicious document is compared with a set of other documents and Intrinsic,  which analysis suspicious document and try to identify sections of text that differ in terms of wording and structure from the rest of the text. In this research we will conduct a theoretical study of the most important algorithms used in detecting plagiarism and comparing this algorithm, based on several factors such as the method of matching, the factors that affect the results of each method and the accuracy of the results.